2017
DOI: 10.1111/acel.12677
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy with the TRF1 telomere gene rescues decreased TRF1 levels with aging and prolongs mouse health span

Abstract: SummaryThe shelterin complex protects telomeres by preventing them from being degraded and recognized as double‐strand DNA breaks. TRF1 is an essential component of shelterin, with important roles in telomere protection and telomere replication. We previously showed that TRF1 deficiency in the context of different mouse tissues leads to loss of tissue homeostasis owing to impaired stem cell function. Here, we show that TRF1 levels decrease during organismal aging both in mice and in humans. We further show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 82 publications
(116 reference statements)
4
16
0
Order By: Relevance
“…In our study, gene expression analyses of YMSCs versus OMSCs revealed that TPP1 was likely to be involved in the process of aging ( Supplementary Figure 2A). Numerous studies have found that the levels of shelterin proteins that directly interact with TPP1, such as TRF1 and POT1, are decreased in aging (Derevyanko et al, 2017;Hosokawa et al, 2017). In the present study, the key role of TPP1 in enhancing therapeutic properties of OMSCs was demonstrated.…”
Section: Discussionsupporting
confidence: 55%
“…In our study, gene expression analyses of YMSCs versus OMSCs revealed that TPP1 was likely to be involved in the process of aging ( Supplementary Figure 2A). Numerous studies have found that the levels of shelterin proteins that directly interact with TPP1, such as TRF1 and POT1, are decreased in aging (Derevyanko et al, 2017;Hosokawa et al, 2017). In the present study, the key role of TPP1 in enhancing therapeutic properties of OMSCs was demonstrated.…”
Section: Discussionsupporting
confidence: 55%
“…Data were analyzed with Microsoft Excel (Microsoft). Telomere fluorescence values were converted into kilobases by external calibration with the CCRF-CEM (7.5 kb), L5178Y-S (10.2 kb), and L5178Y-R (79.7 kb) cell lines (43, 44).…”
Section: Methodsmentioning
confidence: 99%
“…Thickness of the subcutaneous fat layer was measured as previously described 61 . Briefly, a total of 30 measurements were performed on 2 back sections of the skin for each mouse around 100 weeks old.…”
Section: Methodsmentioning
confidence: 99%